Civil society, NGDOs and social development: Changing the rules of the game - Alan Fowler (United Nations Research Institute for Social Development (UNRISD), 2000)
This paper broadly evaluates the role and performance of non-governmental development organizations (NGDOs) in promoting social development before and since the 1995 World Summit for Social Development. Two kinds of analysis and recommendations are offered. The first concerns the practices of NGDOs and their relationships with other "partners in development". The second focuses on the deep-rooted pathologies of the aid system that condition the form and effectiveness of many development interventions not only by NGDOs but also by the larger universe of entities comprising civil society organizations (CSOs). This review concludes that, in the absence of thoroughgoing reform, the aid system will continue to hinder mobilization by the larger civil society with NGDOs to bring about genuine development in the Third World. The concept of civil society has altered development thinking and practice in the major donor countries. However, the Western image of civil society that donors employ does not necessarily apply to civil societies elsewhere. This has serious consequences for efforts to mobilize civil society organizations in developing countries. In practice, donors need to have a much deeper understanding of the configuration and capacity of civil society in the specific locations where they intend to intervene. Donors must also recognize that NGDO efforts, while useful, are limited, and that they cannot substitute for those of the wider civil society. The tasks NGDOs set for themselves, and the expectations of those that finance them, are complex and (probably too) demanding. They cover most facets of social development: reducing poverty and exclusion; improving access to basic services; conflict prevention; fostering democracy; influencing public policies, etc. NGDOs also function at multiple levels, from the individual, through households and intermediary institutions into the arena of international relations, conventions and commitments. In doing so, they may touch some 20 per cent of the world's poor. However, evidence suggests that the NGDO contribution to social change is less substantial and durable than imagined. NGDOs would like to do better and are doing something about it themselves. However, they are limited in this by the unfair, power-imbalanced and donor-serving framework of aid that they operate in. At the same time, NGDOs remain substantially aid-dependent and vulnerable, which can result in questionable motivations and behaviour. For NGDOs to improve their contributions in mobilizing for development, they must better learn to: understand and overcome the factors undermining their efforts; work differently with communities to ensure that change is sustained; develop an ability to cope with relative powerlessness within the "partnerships" that are possible in an unreformed aid system; improve relations between themselves; alter Northern NGDOs' roles vis-à-vis Southern partners and their own national constituencies, and work together with all kinds of NGDOs in coalitions and networks; broaden and bring enduring structure into interactions with wider civil society; interface more broadly with national and local government; operate in the international arena with downward accountability, while adopting advocacy strategies that do not undermine domestic governance or provoke a government "backlash". But structural features of the international aid system limit NGDOs' capacity for self-improvement. Under existing rules, most recipients of aid are relatively powerless and are kept that way. The distorted language of "partnership" is a current example of how rhetoric masks major disparities in power and the maintenance of dependency. And this power imbalance generates perverse incentives for aid recipients. It blocks their necessary ownership of and commitment to change. Six reforms are proposed to attenuate or remove the institutional dysfunctions of aid, and hence make feasible the possibilities for NGDOs to work with diverse CSOs on a larger scale. First, bring greater equity, co-responsibility and ownership into the aid process. Trust funds, or similar mechanisms, have often been proposed and should be implemented. These should create an appropriate distance between the giver and receiver of aid, set within a transparent governance framework. Second, recognize relationships other than "partnership". The aid community requires an array of relationships, named for what they are, each designed to serve different purposes. Different relationships require the open negotiation of different rights and obligations of the parties involved. Third, establish "honest brokers" along the lines of an Ombudsperson, as is now being considered by agencies working in humanitarian and emergency operations. Fourth, prevent "development mono-culture" by encouraging NGDOs to do what they should do best: work with local agents of change to understand and promote integrative, cross-cutting, thematic, participatory and innovative approaches to development, tailored to specific situations. This goes against the current trend of forcing NGDOs to conform to official standards and methods, often prescribed along technical, sectoral lines favoured by the donor. Fifth, improve social development practice by incorporating into interventions a deeper understanding of the interrelationships among social and economic change, the evolution of civic participation, the role and kinds of capacity building needed by CSOs, etc. The meaning of this is made clear by an example of a promising approach to capacity building. Finally, expand relations with civil society on the basis of dialogue and building effective relations between diverse actors at multiple levels. Institutional mapping is one way of identifying entry points for, and obtaining, this type of engagement. The aid system has not demonstrated an ability to reform its fundamental principles and structures. Should it continue this way, NGDOs' credibility when engaging with CSOs will be further compromised. It is not a question of not knowing what needs to be done. Necessary reforms are readily apparent. The problem is that failure to move as needed stems from a donor predisposition to prioritize domestic interests over those of recipients who remain in second place and second class. This may satisfy tax payers' need to see how they themselves benefit from their aid. Nevertheless, this stance is deficient when the same taxpayers ask what is actually being achieved on the ground. They want both home benefits and overseas results. Consequently, poor performance will eventually result in lost credibility at both ends of the aid chain. This must not be allowed to happen. People who are poor and marginalized, and in whose name the system operates, have a fundamental right that this not occur.
Keywords: 330